Analisis Strategi Promosi Kredit Pemilikan Rumah (KPR) Sistem Konvensional Dan Syariah (Studi Kasus : BTN Dan BTN Syariah Kantor Cabang Solo) - Mukhamad Najib; Jono M. Munandar; Agustina Setiyawati (Institute for Research and Community Empowerment (LPPM TAZKIA), 2008)
Residence is one of the primary needs for human being’s life, besides food, clothing, education, and healthy. Many of banks now, have started to offer a residence service product (Kredit Pemilikan Rumah, KPR). As one of the biggest bank in Indonesia, Bank Tabungan Negara (BTN) has an advantage as a pioneer to provide such KPR. To compete with other banks, KPR BTN (including BTN Konvensional and BTN Sharia branch offi ce Solo), as one of the branch unit of Central BTN, has to do strategic promotion effectively so that BTN can come up with their brand image and makes a strong position in market. The aims of this research are: (1). To learn about the promotion activity being used by BTN and BTN Sharia branch offi ce Solo; (2). To identify factors which develop a promotion strategy in BTN and BTN Sharia branch office Solo; (3). To analyze an alternative promotion strategy that might effective to be applied in both BTN and BTN Sharia branch Solo. This research used primary and secondary data. The primary data was collected through out interview and questionnaire while secondary data was obtained from company’s information, literature and electronic publication. In the process of data analysis, it will use factor analysis and Analytical Hierarchy Process using Expert Choice 2000 and Microsoft Excel.BTN and BTN Sharia branch offi ce Solo develop the KPR’s promotion with advertising, sales promotion, publicity and public relation, personal selling, marketing and direct selling. The results of this analysis clearly fi ng out that promotion strategy of BTN branch offi ce Solo is set by fi ve factors, such as market characteristic, facility and equipment, consumer’s characteristic, competition, and company’s Segmenting, Targeting, and Positioning (STP). While, the factors of promotion strategy in BTN Sharia branch office Solo consist of competition, promotion budget, consumer’s characteristic, human research and other marketing mix except promotion. The alternatives which can be pursued are BTN branch offi ces Solo have to increase the advertising activity as the main alternative strategy. The alternative strategy for BTN Sharia branch offi ce Solo is to increase the publicity and public relation as the main strategy alternative.Keywords: Residence Service Product (KPR), Promotion Strategy.